THE MENTAL IMAGE OF AMERICAN SERIES AND FILMS AMONG ARAB YOUTH: A FIELD STUDY ON THE JORDANIAN AND KUWAITI YOUTH - Mohammed Qudah; Rajhi Mnawr (European Scientific Journal, ESJ, 2014)
This study aimed at identifying the mental image of American series and films among Jordanian and Kuwaiti youth and the extent of their impact on the sample. The study was conducted on a sample of 1827 individuals. The study showed that the category of watching for 2-3 hours ranked first at a rate of 46.6%, and individual viewing ranked first by 42.3%, and thus the series and films features were high. The films which are bearing the quality of excitement are ranked first at a mean of 4.26, and the courage quality of some heroes came in the first place at a mean of 3.99 .The American series and films which achieved revenues in millions came in the first place at a mean of 4.24. The study showed that there are significant statistical relationships among the variables: age, place of residence, citizenship, and the features of American series and films.